Coups, regime transitions, and institutional change - Daniel L. Bennett; Christian Bjørnskov; Stephen F. Gohmann (Research Institute of Industrial Economics (IFN), 2019)
Coups and regime transitions are events that typically are intended to change the basic institutional framework of a country. Which specific policies change and the consequences of these changes nevertheless remains largely unknown. Change after a coup or transition implies that some form of political or judiciary barrier has been erected or removed. We therefore focus on what happens to the quality of judicial institutions and political corruption around coup attempts and other types of regime transitions. We hypothesize that when coups are conducted by members of the incumbent political elite, they are likely to remove barriers to change while coup makers outside of the ruling elite are more likely to do the opposite and thus protect themselves from what remains of the elite in the political system. Using the Bjørnskov-Rode coup data, our results suggest that successful coups are associated with degradation of institutions, with successful military coups in particular having a significant negative effect. Results are more varied for civilian coups where we find indications of differences depending on whether the coup makers are part of a political elite or not.
Keywords: P16; P26; O43; 330; Coups; Institutional Quality; Autocracy; Corruption; Judicial Constraints; Regime Transition